Project portfolio management in small context in software industry: A systematic literature review - Linares, J.; Melendez, K.; Flores, L.; Dávila, A. (Springer Verlag, 2018)
In recent years, the software industry in Latin America, mostly consisted of small companies, has shown a notable increase in its operations. However, the practices they use do not allow them to achieve sustainable growth over time. In particular, one aspect that stands out is the disorder that presents inside the company when managing multiple projects with a very small human team. This paper seeks to identify experiences of application of models related to portfolio management in small contexts in the software industry. The study is carried out through a systematic literature review in relevant digital repositories. We have found 60 primary studies obtained in the search in the considered databases. Primary studies show that project portfolio management models present difficulties in their adoption in small contexts. In addition, there are few studies that refer to experiences of application of portfolio management models in small context in the software industry and point out that a relevant aspect for non-adoption is the lack of understanding of the models in their original proposal.
Keywords: Context (archaeology); Portfolio; Project portfolio management; Computer science; Business; Knowledge management; Project management; Engineering; Systems engineering; Geography; https://purl.org/pe-repo/ocde/ford#5.02.04